The Double German Transformation: Changing Male Employment Patterns in East and West Germany - Julia Simonson; Laura Romeu Gordo; Nadiya Kelle (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
Before the 90s, men's employment careers in East and West Germany were quite similar, despite their widely differing institutional settings. Before reunification, employment biographies were mainly dominated by full-time employment in both East and West. After 1989 the GDR was incorporated into the Federal Republic of Germany and almost all East German institutions were supplanted by adapted West German institutions. In the present paper we use SOEP data to analyse whether the East German labour market has converged completely with that of West Germany, following the same pattern of flexibilization and de-standardization, or if East Germany has even overtaken the West in this regard. Weobserve evidence of inhomogenization and pluralization in employment biographies in both regions. However, these trends are more pronounced in East Germany. As a result, employment biographies of younger men are more pluralised and less homogeneous in East Germany than in the West.
Keywords: 330; Cohort comparison; Cluster analysis; German transformation; Inhomogenization of employment biographies; Optimal matching; Pluralization of employment biographies; Sequence analysis; SOEP; Männliche Arbeitskräfte; Erwerbsverlauf; Wirtschaftliche Anpassung; Ostdeutschland; Vergleich; Westdeutsche Bundesländer; Deutschland